2015
DOI: 10.1007/s11517-015-1392-6
|View full text |Cite
|
Sign up to set email alerts
|

Combining femoral and acetabular parameters in femoroacetabular impingement: the omega surface

Abstract: The concept of femoroacetabular impingement (FAI) proposes the development of hip osteoarthritis through motion-induced damage to the acetabular cartilage and labrum. Thus, dynamic interaction of the proximal femur and acetabulum is the crux of FAI. Several types of FAI can be distinguished, but FAI classification is mostly done with separate parameters for acetabular and femoral morphology on planar images, without direct representation of the femoroacetabular interaction. Five main parameters influence impin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…Our results for the osseous ROM simulation match well with the literature for osseous collision detection and highlight the validity of our data. 2,3,39 Based on different software and algorithms for collision detection, flexion of 110°± 7° and IR of 19°± 6° were reported for hips with anterior FAI. 1 Another study reported flexion of 107°± 12° and IR of 19°± 13° for hips with anterior FAI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results for the osseous ROM simulation match well with the literature for osseous collision detection and highlight the validity of our data. 2,3,39 Based on different software and algorithms for collision detection, flexion of 110°± 7° and IR of 19°± 6° were reported for hips with anterior FAI. 1 Another study reported flexion of 107°± 12° and IR of 19°± 13° for hips with anterior FAI.…”
Section: Discussionmentioning
confidence: 99%
“…However, this is also the case for published ROM results using different collision detection softwares. 2,3 This method has also been applied to hips with different conditions, including dysplastic hips, 21,22,52 hips with high FV, 49 and hips with post-LCPD deformities. 56 The application of this method to various hip conditions highlights the validity of the software for collision detection used in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…However, this is also the case for published ROM results using different collision detection softwares. 4,5 The method used in the current study has been applied to hips with different pathomorphologic conditions, including dysplastic hips, 57 hips with valgus morphology combined with increased femoral torsion, 54 and hips with Legg-Calvé-Perthes disease or post-Perthes deformities. 60 The application of this method to various hip morphologic conditions and deformities emphasizes the validity of the software for collision detection used in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a femoral head classified as having cam morphology on account of an alpha angle greater than 55° (Fig. 5a) in reality may not suffer any functional impingement due to the relatively shallow acetabulum with which it is interacting [57]. Likewise, an acetabulum considered to exhibit pincer morphology on account of an increased lateral center edge angle (Fig.…”
Section: Etiology and Risk Factors For Hip Oamentioning
confidence: 99%